2014
DOI: 10.3766/jaaa.25.6.9
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Spectral Resolution, Working Memory, and Audibility in Explaining Variance in Susceptibility to Temporal Envelope Distortion

Abstract: Background Several studies have shown that hearing thresholds alone cannot adequately predict listeners' success with hearing-aid amplification. Furthermore, previous studies have shown marked differences in listeners' susceptibility to distortions introduced by certain nonlinear amplification parameters. Purpose The purpose of this study was to examine the role of spectral resolution, working memory, and audibility in explaining perceptual susceptibility to temporal envelope and other hearing-aid compressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 60 publications
1
17
0
Order By: Relevance
“…The idea that listeners with hearing loss will be forced to shift reliance to temporal cues has been put forth in several papers (Boothroyd, Springer, Smith, & Schulman, 1988; Christensen & Humes, 1997; Davies-Venn & Souza, 2014; Davies-Venn, Souza, Brennan, & Stecker, 2009; Souza, Jenstad, & Folino, 2005). That hypothesis relies, in part, on the idea that temporal cues will be more resistant to degradation from hearing loss than spectral cues, provided the listener can access a sufficiently wide signal bandwidth.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The idea that listeners with hearing loss will be forced to shift reliance to temporal cues has been put forth in several papers (Boothroyd, Springer, Smith, & Schulman, 1988; Christensen & Humes, 1997; Davies-Venn & Souza, 2014; Davies-Venn, Souza, Brennan, & Stecker, 2009; Souza, Jenstad, & Folino, 2005). That hypothesis relies, in part, on the idea that temporal cues will be more resistant to degradation from hearing loss than spectral cues, provided the listener can access a sufficiently wide signal bandwidth.…”
mentioning
confidence: 99%
“…Without this distinction, a common rehabilitation approach might be to use fast-acting compression amplification to improve audibility of low-intensity phonemes. Because that type of amplification would also distort temporal envelope cues (Jenstad & Souza, 2005), it is possible that such a strategy may be detrimental to the listener who depends to a greater extent on temporal cues (Davies-Venn & Souza, 2014). Conversely, use of a high number of compression channels—which may improve audibility at the expense of smoothed frequency contrasts (Bor, Souza, & Wright, 2008)--may be detrimental to the listener who depends to a greater extent on spectral cues.…”
mentioning
confidence: 99%
“…This has been validated in correlational studies, in which spectral ripple has been shown to relate to other behavioral estimates of frequency selectivity including tone detection in notched noise and high-rate spectral modulation detection. 50,51 Spectral ripple is particularly suitable to assess frequency selectivity in listeners with cochlear implants and severe hearing impairment because the stimuli can be presented in a narrow dynamic range. All other measures of frequency selectivity require increasing the level of a signal until another signal that differs in frequency or time becomes inaudible, and the increase in level can approach the loudness discomfort level of a listener with a limited dynamic range.…”
Section: Spectral Ripplementioning
confidence: 99%
“…[98][99][100] Some of those authors also have noted variability among individuals, such that some seem more sensitive to the effect than others. 98,101 Others have noted that the reduced benefit of amplitude compression is associated with phoneme confusions that depend on TE 51,102 and that the effect is reduced by using longer time constants which minimize envelope distortion. 103 Following from such findings, some commercial hearing aids now employ envelope-preserving processing for listeners with severe or profound loss.…”
Section: Speech Recognition In Listeners With Severe Hearing Lossmentioning
confidence: 99%
“…Recent research has suggested a relationship between cognitive ability and hearing aid setting in older users. With wide dynamic range compression, which is a common processing feature in most digital hearing aids, listeners with lower working memory capacity have more difficulty understanding speech processed by wide dynamic range compression with fast release time than with slow release time (Davies-Venn & Souza, 2014;Foo, Rudner, Rönnberg, & Lunner, 2007;Lunner & Sundewall-Thorén, 2007;Ohlenforst, Souza, & MacDonald, 2015;Souza & Sirow, 2014). Although cognitive ability, such as working memory capacity, is a significant factor for choosing individual release time setting, the time and resources needed to quantify cognitive ability are potential barriers for implementing cognitive tests in a clinical setting.…”
Section: Memory Orientationmentioning
confidence: 99%